2013
DOI: 10.19026/rjaset.6.4089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Pollution in Koluama Area, Niger Delta Area, Nigeria Fish Species Composition, Histology, Shrimp Fishery and Fishing Gear Type

Abstract: The effect of water pollution in Koluama Area in the Niger Delta region of Nigeria to determine its effects on fish species composition, histology, shrimp fishery and fishing gear type. A total of twenty (20) species belonging to eleven (11) families were recorded. Strongylura senegalensis, Lagocephalus laevigatus, Tarpon atlantica, Pristis pristis, Galeoides decadatylus and Butis koilomatodon were rare. Ephippion guttifer, Chaetodipterus goreensis, Sardinella maderensis, Sardinella aurita, Liza falcipinnis, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…This is a region where exploitation of oil and gas resources by Multinational Oil Corporations (MNOCs) have been ongoing for the past fifty decades. Various studies have also shown that their operations severely impact on the major habitats -the Atlantic Ocean, seas and estuaries, creeks and mangrove forests among others in the region [17]. The impact on the ecosystems is so huge that it affects the traditional economy and welfare of the coastal communities.…”
Section: Relevance Of the Mpas' Initiative In Nigeria's Niger Deltamentioning
confidence: 99%
See 1 more Smart Citation
“…This is a region where exploitation of oil and gas resources by Multinational Oil Corporations (MNOCs) have been ongoing for the past fifty decades. Various studies have also shown that their operations severely impact on the major habitats -the Atlantic Ocean, seas and estuaries, creeks and mangrove forests among others in the region [17]. The impact on the ecosystems is so huge that it affects the traditional economy and welfare of the coastal communities.…”
Section: Relevance Of the Mpas' Initiative In Nigeria's Niger Deltamentioning
confidence: 99%
“…More than that, oil spillages badly affect the livelihoods of communities and individuals, especially coastal communities and fisher folks [17]. This is because the traditional economy of the Niger Delta people depends mostly on environmental resources.…”
Section: Relevance Of the Mpas' Initiative In Nigeria's Niger Deltamentioning
confidence: 99%
“…Fishes have been widely studied in surface water resources in several water resources in the Niger Delta. [41][42][43][44][45] Fish composition frequently found in surface water includes both shelled and fin fish depending on the habitat. In the present situation the fish composition, diversity and abundance is on the decreasing trend especially in surface water resources with high level of human interference.…”
Section: Fishesmentioning
confidence: 99%
“…The region is a home of several plant species [40] and wildlife including reptiles, mammals, avian fauna among others [40,48]. Bayelsa state has several species of fish fauna including shelled and fin fish and some of them have been documented by Ogamba et al [49 -55], Abowei and Hart [56], Abowei and Ogamba [57], Abowei et al [58], Seiyaboh et al [59 -61]. Other aquatic resources found in the region include planktons [62], aquatic mammals, sea birds among others [4].…”
Section: Bayelsa State: Geology Meteorology and Ecologymentioning
confidence: 99%